2015
DOI: 10.1136/bjophthalmol-2014-306481
|View full text |Cite
|
Sign up to set email alerts
|

Dry eye symptoms align more closely to non-ocular conditions than to tear film parameters

Abstract: Dry eye symptoms more closely align to non-ocular pain, depression and PTSD than to tear film parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 24 publications
3
89
0
5
Order By: Relevance
“…Mental health abnormalities are often comorbid with chronic pain conditions,21 therefore their association with DE symptoms and discordance is not surprising. Strong correlations between DE symptoms, depression, anxiety and PTSD versus only weak correlations seen between symptoms and tear film measures22 imply DE symptoms are more strongly connected to mental health metrics than ocular surface findings.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health abnormalities are often comorbid with chronic pain conditions,21 therefore their association with DE symptoms and discordance is not surprising. Strong correlations between DE symptoms, depression, anxiety and PTSD versus only weak correlations seen between symptoms and tear film measures22 imply DE symptoms are more strongly connected to mental health metrics than ocular surface findings.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our prior data, 24 features suggestive of NOP were assessed using four questions: (1) presence of spontaneous burning ocular pain, presence of evoked pain, including ocular pain caused or increased by (2) wind, (3) light and (4) air temperature (air conditioned/warm weather), with all responses rated on a scale from 0 to 10. Using a two-step cluster analysis based on burning, sensitivity to light, wind and temperature, the patient population was divided into two groups that were significantly different from each other regarding these NOP complaints and were subsequently termed 'high NOP' and 'low NOP' groups.…”
Section: Nop Complaintsmentioning
confidence: 99%
“…23 We previously demonstrated that DE symptom severity correlated with severity of pain elsewhere in the body (non-ocular), depression and post-traumatic stress disease (PTSD) more strongly than it did with ocular surface parameters. 24 Taking this idea a step further, in this paper, we test our hypothesis by classifying patients with DE symptoms into groups based on complaints suggestive of NOP. We then compared features of CSS ( pain ratings, comorbid pain conditions and mental health indices) between these groups.…”
Section: Introductionmentioning
confidence: 99%
“…In another study on normal subjects, rates of ocular surface cooling was found to be positively correlated to fluorescein tear thinning and break-up [42][43][44][45]. Simultaneous imaging of OST and fluorescein adopted in these studies [46][47][48] indicated some improvements in methodology to study OST and tear film behaviour at the same time. Pattmöller et al [43], on the other hand, reported no correlation between corneal temperatures with other ocular parameters such as corneal thickness, endothelial cell density and anterior chamber depth in normal subjects.…”
Section: Correlation Between T4 Metrics and Signs And Symptoms For Drmentioning
confidence: 99%
“…Indeed, it was reported that up to 40% of patients had symptom and clinical sign discordance [46]. A more recent study has shown that dry eye symptoms aligned more closely to non-ocular pain, depression and post-traumatic stress disorder than tear film parameters [48].…”
Section: Correlation Between T4 Metrics and Signs And Symptoms For Drmentioning
confidence: 99%